The Differences in Subjective Well-being in Dry Land Farmers Assessed From Land Owners and Tenant in Manulai II Village - JUBLINA MARSELINA NOMATE; Yeni Damayanti; Indra Y Kiling; Imelda F. E. Manurung (Universitas Nusa Cendana, 2021)
Abstrac. A farmer's welfare can vary from farmer to farmer. Where a farmer can be said to be prosperous if the farmer can evaluate his life in a positive way and is satisfied with the life he has. Where life satisfaction is individual satisfaction that is comprehensive and very basic, as well as how the individual sees himself and his life. Subjective well-being also consists of two components, namely, a cognitive component (life satisfaction) and an affective component. The affective component consists of two parts, namely positive and negative effects. This study aims to see differences in the subjective well-being of dry land farmers in terms of land owners and renters. The subjects in this study were 100 farmers in Manulai II Village. Subjective well-being was measured using a research scale conducted by Hanggoro , 2015. The research hypothesis was tenant using a different test . The results of the analysis show that there are differences in the subjective well-being of land farmers and tenant farmers in Manulai II Village. Where sig (2-tailed) at 0, 00 .